PENGEMBANGAN VIDEO BAHAN AJAR KESELAMATAN DAN KESEHATAN KERJA PADA MATA PELAJARAN TEKNOLOGI DASAR OTOMOTIF KELAS X OTOMOTIF SMK - Iqbal Billy Ramadhan; Samidjo (JURNAL VOKASI DEWANTARA (JVD), 2025)
This study aims to (1) Know the characteristics of Occupational Health and Safety (OSH)learning videos in the subject of Automotive Basic Technology Class X Automotive atYogyakarta Industry Vocational High School, (2) Know the feasibility of OSH learningvideos on Automotive Basic Technology subjects Class X Automotive at Yogyakarta IndustryVocational High School, (3) Know the response students on the Occupational Health andSafety (K3) learning video in the subject of Automotive Basic Technology class X Automotiveat the Industrial Vocational School of Yogyakarta.This research is a research and development (R&D) with a 4D (Four-D) development modelconsisting of the Define, Design, Development, Disseminate stages. The development mediais in the form of learning videos. The subject of this research is class X automotive at SMKIndustry Yogyakarta. The object of this research is the K3 learning video. Media feasibilityassessment is carried out by media experts and material experts. The instrument used is aquestionnaire / questionnaire. Data analysis techniques using quantitative descriptiveanalysis. The results of the study show that: this research produces K3 learning videos, K3learning videos are used based on the results of the material expert validation with "veryfeasible" and the results of the media expert validation score are ''worthy'' Student responsesindicate the category is very feasible to use with "very feasible"